Pengaruh Ketebalan Mulsa Organik Terhadap Pertumbuhan Dan Hasil Jagung Manis (Zea Mays Saccharata Sturt.) - Desti Kurniawan Gulo; Helmin Parida Zebua; Dian Agung Sanora Laia; Elikana Lase (CV. SINAR HOWUHOWU, 2026)
Sweet corn (Zea mays saccharata Sturt.) is a horticultural commodity with high economic value; however, its productivity remains relatively low due to environmental stress and weed competition. Organic mulch is an environmentally friendly technology that can enhance crop productivity, yet the optimal mulch thickness for sweet corn cultivation has not been well established. This study aimed to evaluate the effect of organic mulch thickness on the growth and yield of sweet corn and to determine the optimal mulch thickness. The experiment was conducted using a non-factorial Randomized Complete Block Design (RCBD) with four levels of rice straw mulch thickness: M0 (no mulch, 0 cm), M1 (3 cm), M2 (6 cm), and M3 (9 cm). Each treatment was replicated six times. The observed parameters included plant height, number of leaves, stem diameter, husked ear weight, unhusked ear weight, and number of kernel rows per ear. The results showed that organic mulch thickness significantly affected all observed parameters. Application of rice straw mulch at a thickness of 6–9 cm effectively improved the growth and yield of sweet corn, with 9 cm being optimal for ear weight and 6 cm being optimal for the number of kernel rows.